Field Evaluation and Serological Detection of Potato Leaf Roll Virus in Potato Germplasm - Ashraf, Waqas; Habib, Amer; Zeshan, Muhammad Ahmad; Amin, Amina; Ali, Safdar; Mohsin, Muhammad; Khan, Atta ur Rehman; Ghani, Muhammad Usman; Khan, Awais Ahmed; Hassan, Syed Wasim (Asian Journal of Biological and Life Sciences, 2020)
Potato tuber (Solanum tuberosumL.), a main staple food ranked 4thin the world followed by rice, wheat and maize. Potato leaf roll virus (PLRV) is the most vital pathogen of potato in Pakistan that cause 90% losses and transmitted by green peach aphid (Myzus persicae).Twenty cultivars of potato were screened against PLRV. Twenty samples were collected on the basis of symptoms and tested by serological assay (DAS-ELISA). Disease incidence was calculated using prescribed formulae. Among all tested cultivars, ten cultivars were found resistant, five cultivars moderately resistant, one cultivar moderately susceptible and two cultivars highly susceptible. Detection of PLRV was done by DAS-ELISA which indicated that three cultivars found resistant, eleven moderately resistant, two moderately susceptible and four cultivars were susceptible.
Keywords: Cultivars; ELISA; Management; PLRV; Resistance; Screening